Question
upstudy study bank question image url

a) Solve the unknown in each of the following: 8) \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \)

Ask by Johnson Joseph. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x=4 \)

Solution

Solve the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x}\) - step1: Find the domain: \(\frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x},x \in \left(-\infty,2\right)\cup \left(2,3\right)\cup \left(3,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\frac{x}{x-2}\times \left(x-2\right)\left(-x+3\right)=\left(\frac{1}{x-3}-\frac{2}{2-x}\right)\left(x-2\right)\left(-x+3\right)\) - step3: Simplify the equation: \(-x^{2}+3x=8-3x\) - step4: Move the expression to the left side: \(-x^{2}+3x-\left(8-3x\right)=0\) - step5: Calculate: \(-x^{2}+6x-8=0\) - step6: Factor the expression: \(\left(-x+4\right)\left(x-2\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-x+4=0\\&x-2=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=4\\&x=2\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=4\\&x=2\end{align},x \in \left(-\infty,2\right)\cup \left(2,3\right)\cup \left(3,+\infty\right)\) - step10: Find the intersection: \(x=4\) The solution to the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \) is \( x=4 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( \frac{x}{x-2}=\frac{1}{x-3}-\frac{2}{2-x} \), first simplify the right side. Notice that \( \frac{2}{2-x} \) can be rewritten as \( -\frac{2}{x-2} \) since they are negatives. Thus, the equation becomes: \[ \frac{x}{x-2} = \frac{1}{x-3} + \frac{2}{x-2} \] Now, combine the fractions on the right-hand side under a common denominator \( (x-3)(x-2) \): \[ \frac{x}{x-2} = \frac{(x-2) + 2(x-3)}{(x-3)(x-2)} \] This simplifies to: \[ \frac{x}{x-2} = \frac{x-2+2x-6}{(x-3)(x-2)} = \frac{3x-8}{(x-3)(x-2)} \] Now, cross-multiply to eliminate the fractions: \[ x(x-3) = (x-2)(3x-8) \] Expanding both sides gives: \[ x^2 - 3x = 3x^2 - 8x - 6x + 16 \] \[ x^2 - 3x = 3x^2 - 14x + 16 \] Rearranging the terms leads to: \[ 0 = 2x^2 - 11x + 16 \] Now, apply the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 16}}{2 \cdot 2} = \frac{11 \pm \sqrt{121 - 128}}{4} = \frac{11 \pm \sqrt{-7}}{4} \] Since the discriminant is negative, we end up with two complex solutions: \[ x = \frac{11 \pm i\sqrt{7}}{4} \] Thus, the solutions are: \[ x = \frac{11}{4} + \frac{i\sqrt{7}}{4} \quad \text{and} \quad x = \frac{11}{4} - \frac{i\sqrt{7}}{4} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy